MENELISIK PERAN TENAGA AHLI ANGGOTA LEGISLATIF - Permana, Yogi Setya; Adaba, Pandu Yuhsina (Jurnal Penelitian Politik, 2025)
Performance oftheparliament would be maximal ifit s been back up with optimal support system Part ofthe support systems is parliamentary expert staff As a matter offact performance and role ofthe expert staffs as part ofsupporting Indonesia s parliamentary is not in optimal condition The condition is due to absence ofclear and detail regulation on the role anffunction ofparliament expert staff As a result ofthat condition many distortions in role andfunction ofexpert staffhas been dailyfact in the parliament This paper is to analyze thatproblem and give some recommendation related to the problem